Occupational ergonomics: Work posture among Brazilian dental students - Garcia, Patricia Petromilli Nordi Sasso [UNESP]; Wajngarten, D. [UNESP]; Gottardello, A. C A [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP] (My University, 2013)
This study involved observational assessment of work posture in relation to recommended ergonomic posture the requirements necessary for ergonomic posture among students in the final year of a degree program at the School of Dentistry of Araraquara-UNESP/Brazil (n =73) and investigation of the association of work posture with sex, the type of procedure, four-handed dentistry, and the region of the mouth being treated. The work posture of the students during 250 clinical procedures was observed by means of pictures. Each procedure received a posture classification: Adequate, partially adequate, or inadequate. A descriptive statistical analysis was conducted. The prevalence of final posture classification was calculated using 95% confidence intervals and point estimate. Associations of interest were studied using the chi-square test, with a 5% significance level. It was concluded that the prevalence of procedures performed with partially adequate posture was high, and that the final work posture classification was not associated with the variables of interest. © 2013 Taylor & Francis Group.
Keywords: Chi-square tests; Clinical procedure; Confidence interval; Degree program; Point estimate; Posture classification; Significance levels; Work postures; Dentistry; Occupational risks; Statistical tests; Students; Ergonomics